Cinemateca 78 (2017)
In a context of urban renewal because of the construction of an elevated train at the city of Bogotá, the border of Avenue Caracas, from 72nd Street to 80th Street presents a great opportunity. The course purpose is to work on the border, in order to respond to the train and begin to renew the sector. The place has a mix of important uses, largely hidden; in this sector there is aso a cultural use that has been growing. In an important block, in Caracas with 76, a film library is proposed, which can show the cultural characteristic of the place and can allow the connection of the flows to the interior of the neighborhood. The cinema project seeks to generate a cultural experience for the city. A cinema library is usually linked to the academic field, the idea is to go beyond. When it connects with the city, it can allow a social and cultural space for Bogotá...